To the memory of a teacher. On 85 th anniversary of Herman I. Tarakanov - E.G. Dobrutskaya; F.B. Musaev; M.M. Tareeva (Овощи России)
At department of ecology of All-Russian Research Institute of Vegetable Breeding and Seed Production the adaptive capacity through bean accessions has been analyzed. As a summarized result for 3 years of observation, Rashel and 6 KSI have been determined as cultivar types with high adaptive capacity for a yielding characteristic and seed production. The mentioned types have been proven to be cultivated wide spread in different growing, soil and farming conditions without any risk of yield and quality reduction.